The Effect of Two Low Doses of Aspirin on Whole Blood Thromboxane and Prostacyclin Generation in Healthy Subjects - Davì, G; Custro, N; Novo, S; Mattina, A; Strano, A (Thrombosis and Haemostasis, 1983)
The effects of two low doses of aspirin (20 mg and 100 mg) on prostacyclin and thromboxane formation during whole blood clotting were studied in 8 healthy volunteers.A single 100 mg aspirin dose caused more than 90% reduction of both serum TXB2 and 6-keto-PGF1α; a single 20 mg dose of aspirin inhibited serum TXB2 more than 6-keto-PGF1α but effects on these two products could not be completely dissociated.However, the effect of a single 20 mg aspirin dose on serum TXB2, was of much longer duration than its inhibitory effect on PGI2 synthesis during whole blood clotting.
Keywords: Thromboxane; Prostacyclin; Aspirin